Penjatuhan Pidana Mati Terhadap Pelaku Pembunuhan Berencana Dalam Perspektif Hak Asasi Manusia - Ady, Wisnu Pratomo; Haryono, Waty Suwarty; Saefullah, Saefullah (Universitas Malayati, 2025)
Premeditated murder is punishable by the death penalty in accordance with Article 340 of the Criminal Code. In this article, it is stated that perpetrators of premeditated murder can be threatened with the death penalty, life imprisonment or a maximum prison sentence of 20 years. The problems discussed in this research are why is there still a death penalty imposed by judges in Indonesia? In conclusion, the death penalty is still the heaviest punishment of all punishments in Indonesian positive law. However, after reviewing the existing articles, we found that the right to life and a person's life is absolute. These rights are limited by the rights of other people as well. Because basically violations of human rights are regulated in article 7 of Law Number 26 of 2000 concerning Human Rights Courts, where serious crimes that can be sentenced to death include the crime of premeditated murder. That is why until now, the imposition of the death penalty by a judge is still taking place in Indonesia. The basis of the judge's legal considerations for imposing the death penalty on perpetrators of premeditated murder in Decision No.19/PID/2023/PT TTE and Decision No.51/PID/2023/PT BJM is appropriate and appropriate, as the criminal elements in Article have been fulfilled 340 of the Criminal Code so that the actions of these heinous perpetrators can be punished.